Pengaruh Green accounting, Kinerja Lingkungan, CSR, Ukuran Perusahaan, dan Profitabilitas terhadap Nilai Perusahaan pada Perusahaan Sektor Pertambangan yang Terdaftar di BEI Periode 2020-2024 - Amilia, Rendi Kiki Rizki; Budi Santoso (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The purpose of this study is to analyze how firm value is influenced by green accounting, environmental performance, Corporate Social Responsibility, firm size, and profitability. The research method used is a multiple linear regression analysis approach. The testing process included panel data regression model tests (Chow test, Hausman test, Lagrange multiplier test), classical assumption tests (normality, multicollinearity, heteroskedasticity, autocorrelation), and hypothesis tests (F-test, t-test, R² test). The research data was sourced from secondary data in annual reports and sustainability reports of mining companies listed on the Indonesia Stock Exchange (IDX) during the period 2020-2024. The analysis results show that the variables of green accounting, company size, and profitability have a negative and significant effect on company value. Meanwhile, the variables of environmental performance and CSR do not affect company value. Simultaneously, all five variables were found to influence firm value, with an Adjusted R-Square contribution of 22%. This finding confirms that increases in firm value are not solely determined by sustainability commitments or asset size.